An appraisal of tertiary home economics education programs in Region 8 - Nical, Rosita Echague (1995)
The main objective of this study was to appraise the effectiveness of the Bachelor of Science in Industrial Education major in Home Economics Education (BSIE-HE) Programs in five vocational-technical schools in Region 8. Descriptive and correlational methods of research were used with 44 senior students, 77 graduates, 43 home economics teachers and 60 employers as respondents purposively sampled. Structured survey questionnaires, observation cum-interview guide and rating sheets were used in gathering the data. The statistical tests used were one-way analysis of variance, t-test and Spearman Rank Correlation. The findings revealed that the total enrollment and graduates for five school years, 1987 to 1992 was 987 and 233, respectively. The course offerings were inadequate. The admission policies were almost the same in the five schools. The teaching staff had appropriate degrees for the subjects they were teaching and majority had taken advanced courses. In-service trainings of faculty members were inadequate; few researches were conducted and very few articles had been published. The facilities and equipment were generally rated adequate but rated inadequate in some. The senior students and graduates had access to the different equipment and facilities of the five schools. Local in-service training showed significant difference. Teaching behavior was manifested to a "great extent". The most used methods of teaching were project, lecture, lecture-discussion, reporting and demonstration. The most effective methods were lecture-discussion and demonstration. Considered most performed and most effective teaching activities were laboratory work and project making. The program was effective in attaining the first two objectives and moderately effective in attaining the third objective. Teaching activities correlated with all areas of competences. Adequacy of buildings correlated significantly and positively with learning competences, while enrollment correlated negatively with earning competences. The employability of the graduates was moderately effective. Realignment of the BSIE-HE curricula is recommended. Other recommendations are: more effective means of promoting the academic program as well as proper monitoring of admission requirements; provision of adequate facilities, equipment and other resources and improve qualifications of teaching staff. Frequent utilization of laboratory work, project making activities and the active methods of teaching in home economics classes such as lecture-discussion and demonstration were also recommended.